- (B^-1)*(A^-1)*(E^-1)*(D*-1)
- (A^-1)*(B^-1)*(D^-1)*(E*-1)
- (ABDE)^-1
- (EDBA)*-1

Answer: Option 1

Explanation:

ABCDE = I BCDE = (A^-1) Pre-Multiplying with A^-1 on both sides CDE = (B^-1)*(A^-1) Pre-Multiplying with B^-1 on both sides CD = (B^-1)*(A^-1)*(E^-1) Post-Multiplying with E^-1 on both sides C = (B^-1)*(A^-1)*(E^-1)*(D^-1) Post-Multiplying with D^-1 on both sides

Previous Question : A = a1 a2 a3
b1 b2 b3
c1 c2 c3
Then, a1*cof(b1) + a2*cof(b2) + a3*cof(b3) =

Next Question : If a row or coloumn of a matrix A undergoes transformation given by Ri+kRj or Ci+kCj respectively, t...

Click here for online test on Matrices

Next Question : If a row or coloumn of a matrix A undergoes transformation given by Ri+kRj or Ci+kCj respectively, t...

Click here for online test on Matrices

- For square matrices A,B,C and D, If AB=AC, then we can write B=C
- Given t(AB) = t(B) * t(A) where t stands for transpose, we can write-
- If the determinant of a matrix A is 1, then it is a-
- A = 0 i i 0 is a-
- A skew-symmetric matrix must-
- If A = 0 0 and B = 0 0 0 0 0 0 0 0 0 0 Then AB -
- Let A = 1 1 3 5 2 6 -2 -1 -3 It is seen that A^3 = 0. So, A is a-
- A = a1 a2 a3 b1 b2 b3 c1 c2 c3 Then, a1*cof(b1) + a2*cof(b2) + a3*cof(b3) =
- Let A,B,C,D,E be n*n matrices, each with non-zero determinant and ABCDE = I, where I = Identity matr...
- If a row or coloumn of a matrix A undergoes transformation given by Ri+kRj or Ci+kCj respectively, t...

While it is true that most people never see or understand the difference they make, or sometimes only imagine their actions having a tiny effect, every single action a person takes has far-reaching consequences.

-Andy Andrews
The Noticer: Sometimes All a Person Needs Is a Little Perspective.